2013
DOI: 10.1213/ane.0b013e3182910c4d
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Intraarticular Lumbar Facet Joint Steroid Injections and Lumbar Facet Joint Radiofrequency Denervation in the Treatment of Low Back Pain

Abstract: Intraarticular steroid infiltration or radiofrequency denervation appear to be a managing option for chronic function-limiting low back pain of facet origin with favorable short- and midterm results in terms of pain relief and function improvement, but improvements were similar in both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
111
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(117 citation statements)
references
References 31 publications
0
111
0
6
Order By: Relevance
“…To date, there is controversy about the effectiveness of intra-articular steroid injections [6] . Recently, several studies were conducted to learn more about the clinical benefit of LFJ infiltration with glucocorticoids in comparison to alternative treatment options [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…To date, there is controversy about the effectiveness of intra-articular steroid injections [6] . Recently, several studies were conducted to learn more about the clinical benefit of LFJ infiltration with glucocorticoids in comparison to alternative treatment options [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…The clinical features of this syndrome are localized back pain or neck pain worsened with extension, improved with extension, and diagnosed with facet blocks. Lumbar facet joint degeneration is a source of chronic low back pain, with an incidence of 15% to 45% among patients with low back pain [27]. On occasion, radiological studies may show facet hypertrophy.…”
Section: Introductionmentioning
confidence: 99%
“…A facet denervation is the treatment of choice. However, a recent publication reported that the efficacy of the steroid injection was equal to radiofrequency denervation [27] Another diagnosis overused by physicians who cannot accurately establish diagnosis is complex regional pain syndrome (CRPS) or reflex sympathetic dystrophy (RSD). Research shows that these patients have nothing more than undetected nerve entrapment syndrome 71%-80% of the time, and they respond to nerve decompression as their sole treatment [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Lumbar facet joint degeneration is a source of chronic low back pain, with an incidence of 15 to 45% among patients with low back pain. 27 On occasion, radiological studies may show facet hypertrophy. One study reported in association between heavy physical activity and the development of CT confirmed lumbar zygapophyseal joint osteoarthritis.…”
mentioning
confidence: 99%
“…However, a recent publication reported that the efficacy of the steroid injection was equal to radiofrequency denervation. 27 Patients are mistakenly told that they have complex regional pain syndrome or reflex sympathetic dystrophy (RSD) at an unconscionably high rate. The clinical presentation of RSD requires circumferential pain (pain all around a limb), in combination with mechanical and thermal allodynia (a painful response to a normally nonpainful stimulus).…”
mentioning
confidence: 99%